2003
DOI: 10.1111/j.1600-0412.2004.00356.x
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric outcomes after cervical ripening by multiple doses of vaginal prostaglandin E2

Abstract: The risk of emergency cesarean section was higher in women who required more than two doses of vaginal prostaglandin E2 for cervical priming compared to induction by one or two doses of vaginal prostaglandin E2 or by amniotomy and oxytocin infusion. These women should be informed regarding the high risk of intrapartum cesarean section, and the option of alternative methods of induction or elective cesarean section should be made available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…It has been suggested that PG gel may be safer than the tablets in GM as its main effect is in cervical ripening and its contractive effect is considered minimal. [14][15][16][17] This study showed that the outcome of Labor with IOL are favorable and comparable with patients in spontaneous Labor. Mecer et al studied the complications and outcomes of elective induction and spontaneous labour and found no difference between the study group and the control group.…”
Section: Resultsmentioning
confidence: 75%
“…It has been suggested that PG gel may be safer than the tablets in GM as its main effect is in cervical ripening and its contractive effect is considered minimal. [14][15][16][17] This study showed that the outcome of Labor with IOL are favorable and comparable with patients in spontaneous Labor. Mecer et al studied the complications and outcomes of elective induction and spontaneous labour and found no difference between the study group and the control group.…”
Section: Resultsmentioning
confidence: 75%
“…However, the risk of an unfavorable delivery outcome in these pregnancies is related to various factors, including the indications for induction, the cervical status and the methods used [2]. Many reports have described the effects of labor induction in a heterogeneous group of patients with several confounding risk factors [3][4][5].…”
Section: Introductionmentioning
confidence: 98%
“…labour induction and spontan. onset of labour in prolonged pregnancy Zaineb T. Alyasin Bas J Surg, 16, March, 2010 ٧٦ delivery outcome in these pregnancies is related to various factors, including the indications for induction, the cervical status and the methods used 6 . Currently the most common reason for induction of labor is prolonged pregnancy 7 .…”
Section: Introductionmentioning
confidence: 99%